Crushing behavior of multi-component conical tubes as energy absorber: A comparative analysis between end-capped and non-capped conical tubes. (1st January 2019) - Jafarian, Nader; Rezvani, Mohammad Javad
Highlights: By creating a multi-component conical tube, the initial peak load decreased. By making a multi-component conical absorber, the maximum crushing load occurred at the end of the collapse process. By increasing the number of segments, SEA in multi-component conical absorber increased in comparison with the simple tubes. Abstract: Design of multi-component absorber is a method to improve the specific energy absorption (SEA) and reduce the peak crushing load at the time of the initial accident. In this study, multi-component conical specimens are made from aluminium in the form of end-capped and non-capped. To do so, a long conical tube is divided into several shorter thin-walled conical portions, so that the thickness, length and mechanical properties of the wall vary along the tube length. The purpose of this new design on the conical absorber is to modify performance of shock absorber including decrease of initial peak crushing load and increase of SEA. Therefore, a series of quasi-static experimental tests are carried out on the end-capped and non-capped multi-component conical tubes and parameters of energy absorption, initial peak load, crush force efficiency and SEA are calculated. The results show that the maximum crushing load in simple conical tubes begins at first folding, while it is shifted to the end of the crushing process in multi-component conical tubes. Also, it is shown that the SEA and the crush force efficiency of the non-capped multi-component specimens were further in comparison with the end-capped ones. Finally, it was found that by using this type of the energy absorber, damage to the main structure and also the occupants of car was decreased.